2023
DOI: 10.3390/app13074319
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Callus and Corns Removal Treatments on Foot Geometry Parameters, Foot Pressure, and Foot Pain Reduction in Women

Abstract: Foot pain and deformities are significant problems that increase with age and are significantly more prevalent in women. Calluses and corns are both common and inconvenient, and the accompanying pain complaints significantly reduce the quality of life. Professional foot care is one of the key elements in the prevention of foot disorders and improves the comfort of people with such problems. The aim of the present research was to assess the impact of podiatry treatments on the foot conditions, including paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…The utility of callous area identification can be extended from wound care to foot care in general. Anto ńczak et al [16] found that podiatry treatments consisting of the removal of hyperkeratosis not only normalized the parameters related to foot geometry and to forefoot pressure on the ground, but also reduced foot pain, thus improving quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of callous area identification can be extended from wound care to foot care in general. Anto ńczak et al [16] found that podiatry treatments consisting of the removal of hyperkeratosis not only normalized the parameters related to foot geometry and to forefoot pressure on the ground, but also reduced foot pain, thus improving quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated gastrocnemius tightness (IGT) is a widely encountered condition associated with various foot pathologies, including metatarsalgia and hallux valgus [1][2][3]. The prevalence of IGT is challenging to determine accurately due to the lack of a consensus definition and validated measuring device [4].…”
Section: Introductionmentioning
confidence: 99%